DAMPAK INVESTASI TERHADAP KETIMPANGAN KESEMPATAN KERJA REGIONAL DI INDONESIA - Lusia Peilouw (Jurnal Kependudukan Indonesia, 2007)
Nuaulu is a tribal community in Maluku. Geographically this community is not isolated as is commonly assumed tribal communities living in remote areas are. Located among non-tribal communities, it is only a few kilometres from the centre of the Maluku Tengah District. However, these communities differ in social provisioning entitlements. This study uses infant mortality to explain social phenomena in the communities. Through a structured survey and literature study, it has found that infant mortality in the Nuaulu population in Rouhua is higher than in the non-Nuaulu population in Makariki. Social factors such as education, health and culture are considered determinants of the mortality together with household economic resources. None of these socio-economic factors works alone but through links among them as analysed using Mosley and Chen's framework (1984). Therefore, I argue that different availability of and access to social services and economic resources are the major reasons for the different trends. Cultural practices are not a problem if social and economic needs are properly satisfied. Political will and the concern of the Government are the crux of the matter in this context. Excluding ethnic communities from social policies makes people within those conununities vulnerable.Keywords: Nuaulu; Ethnicity; Social Policy; Social Exclusion